If the below given equations are true and all the variable are positive integers. a + b + c = 2 1 0 a x + b + c = 2 2 0 a + b x + c = 2 3 0 a + b + c x = 2 4 0
Find 4 9 0 x ( a − 1 + b − 1 + c − 1 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did exactly in the same way.........+1 for the approach.......
a x + b + c = 2 2 0 = 2 1 0 + 1 0 = a + b + c + 1 0 ⟹ a ( x − 1 ) = 1 0 by the same approach using the other 2 equations you get b ( x − 1 ) = 2 0 and c ( x − 1 ) = 3 0 so b ( x − 1 ) = 2 a ( x − 1 ) ⟹ b = 2 a and c ( x − 1 ) = 3 a ( x − 1 ) ⟹ c = 3 a so 6 a = 2 1 0 ⟹ a = 3 5 ⟹ b = 7 0 and c = 1 0 5 . Now that we have the values of a , b , and c , we can now plug them in any equation with x in it: 3 5 x + 7 0 + 1 0 5 = 2 2 0 ⟹ 3 5 x = 4 5 ⟹ x = 7 9 then 4 9 0 ⋅ 7 9 ( 3 5 1 + 7 0 1 + 1 0 5 1 ) and solve it which gives 33. This isn't really a number theory question, just simple algebra(maybe not "that" simple) and it certainly isn't level 3.
Problem Loading...
Note Loading...
Set Loading...
We have a + b + c = 2 1 0
From rest equations we find (by adding the rest)
2 ( a + b + c ) + x ( a + b + c ) = 6 9 0 x = 7 9
We can find from first equation
a + b = 2 1 0 − c b + c = 2 1 0 − a c + a = 2 1 0 − b
Now putting the above given value in the parameter x equations
a ( x − 1 ) = 1 0 b ( x − 1 ) = 2 0 c ( x − 1 ) = 3 0
From these
a : b : c = 1 : 2 : 3
From first a = 3 5 , b = 7 0 , c = 1 0 5
Now we have to find
4 9 0 x ( a − 1 + b − 1 + c − 1 ) 4 9 0 × 7 9 ( 3 5 1 + 7 0 1 + 1 0 5 1 ) = 3 3